Analisis Yuridis Terhadap Diferensiasi Pertanggungjawaban Pidana Dalam Kasus Penganiayaan Yang Dilakukan Secara Bersama-Sama - Tiara Okta Yanti; Aldi Prasetiawan Saputra; Dea Eryan Ananda; Muhammad Armada; Dwi Putri Lestarika (GLOBAL SCIENTS PUBLISHER, 2025)
The application of differentiated criminal liability by investigators in handling collective assault cases represents the implementation of justice and individualization principles in Indonesia’s criminal law system. This principle requires that each offender be held accountable according to their level of culpability, intent, and contribution to the offense. Juridically, the legal basis for applying this differentiation lies in Articles 55 and 56 of the Indonesian Criminal Code (KUHP) concerning participation, Article 170 KUHP concerning group assault, and Articles 1(2) and 7(1)(a) of the Criminal Procedure Code (KUHAP), which authorize investigators to assess and determine the role of each participant. Additionally, this principle is grounded in the constitutional guarantee of justice under Article 28D(1) of the 1945 Constitution of the Republic of Indonesia and the principle of proportionality as stipulated in National Police Regulation No. 6 of 2019 on Criminal Investigation. Through the implementation of differentiated criminal liability, investigators are expected to uphold law enforcement that is fair, professional, and proportional thus preventing over-criminalization and ensuring substantive justice for all individuals involved in joint assault crimes.